Letter (copy) : Imprisonment of Mr. Frank Ryan - Citrine, Walter, 1887-1983
013-0074-001 International WMC/EAB/DT/1047. 14th June, 1940. Mr. B. Reynolds, Chester Trades Council, "Fairholme", 6, Meadows Lane, CHESTER. Dear Mr. Reynolds, IMPRISONMENT OF MR. FRANK RYAN. Thank you for your letter dated 11th June which we received to-day informing me of the terms of a letter which you have addressed to the Spanish Ambassador in London with regard to the imprisonment by the Spanish Authorities of Mr. Frank Ryan of the International Brigade. We understand that Mr. Ryan is a citizen of Eire, and as this question would have to be pursued through diplomatic channels it would seem that an approach from the Eire Government would probably be more suitable than one from the British Government. I appreciate your sentiments in connection with my appointment to the Privy Council and reciprocate your good wishes. Yours sincerely, General Secretary. 292/946/13/74